More direct attacks increase likelihood of goals in 2018- and 2022-Men`s World Cup Soccer Finals - Taha, T.; Orlov, I. (PLOS ONE, 2025)
In soccer, attacking tactics can vary between elaborate, high passing play and play that involves very direct, straight-line action towards the towards the opponent`s goal. It is of considerable interest to individuals involved which type of play is more effective in scoring given that goals are a rare event. We propose a geometric measure of directness (DIR) using the ratio between the straight-line distance from the point where possession begins to the centre of goal, and the total distance covered by the ball during that possession. Using 128 matches from the 2018- and 2022-Men`s World Cup, we analyzed the influence of directness (DIR), speed of the ball traveling towards the goal (SPG) and the starting position of the possession (XPOS) on the likelihoods of shots and goals. A mixed-effect multivariate logistic regression model was used for both analyses. Following model simplification (AIC = 14579.7, R2 = 0.279), the log odds of a shot resulting from a possession was significantly increased by XPOS (ß = 0.019, p < 0.0001), SPG (ß = 0.322, p < 0.0001) and a three-way interaction between DIR, XPOS and SPG (ß = 0.007, p < 0.0001). The likelihood of a shot was decreased by interactions between DIR and XPOS (ß = -0.024, p < 0.0001), DIR and SPG (ß = -0.587, p < 0.0001) and XPOS and SPG (ß = -0.003, p < 0.0001. The model for the likelihood of a goal (AIC = 1736.9, R2 = 0.020) was simple with DIR being the only significant factor (ß = 1.009, p < 0.0001). The results suggest that to increase the likelihood of scoring goals, attacking tactics must be more direct.